(untitled) (Research, Society and Development, 2022)
The Academic Week SIGICar - Semana Acadêmica de Integração, Gestão e Insights de Carreira is an extension action developed by professors and other actors from UFRRJ, Seropédica / RJ, Brasil. SIGICar was proposed as a space for dialogue and sharing of experiences between the various professionals of UFRRJ and the labor market, guided by freedom of expression, to develop a critical sense and provide responsible training to the Administration student and, by extension, in all invited students of the Instituto de Ciências Sociais Aplicadas - ICSA / UFRRJ. A survey was answered by 168 participants (n = 168), among administration students of the institution, among participants (n = 71) and future participants (n = 97) of the event. The research question of the work was: - What formats, themes and career ideas could be offered to students’ University education, in the Administration course, so that their involvement is more participatory and this extension action is able to promote a contribution in professional training and student staff? The new editions of SIGICar should present a greater number of market professionals among the speakers, new activities proposed with prior instructional material distributed, activities in the afternoon and evening, separated by professional cycle. And address mainly the following topics: careers and market and work management, leadership and career guidance processes, and people and small business management.